2022
DOI: 10.1073/pnas.2200841119
|View full text |Cite
|
Sign up to set email alerts
|

Gender-diverse teams produce more novel and higher-impact scientific ideas

Abstract: Science’s changing demographics raise new questions about research team diversity and research outcomes. We study mixed-gender research teams, examining 6.6 million papers published across the medical sciences since 2000 and establishing several core findings. First, the fraction of publications by mixed-gender teams has grown rapidly, yet mixed-gender teams continue to be underrepresented compared to the expectations of a null model. Second, despite their underrepresentation, the publications of mixed-gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 59 publications
0
82
0
1
Order By: Relevance
“…For example, ecological research remains largely dominated by exclusionary Western approaches [ 36 ]. This is despite extensive evidence across multiple fields that diverse teams are more innovative and productive [ 34 , 37 39 ]. In addition, ECOPs from underrepresented communities often experience the intersection of many forms of discrimination, so may face cumulative effects of different barriers [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ecological research remains largely dominated by exclusionary Western approaches [ 36 ]. This is despite extensive evidence across multiple fields that diverse teams are more innovative and productive [ 34 , 37 39 ]. In addition, ECOPs from underrepresented communities often experience the intersection of many forms of discrimination, so may face cumulative effects of different barriers [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gender-diverse teams have higher long-term impact as their expertise diversity increases, and similar results hold for gender-homogeneous teams. Promoting gender diversity in the team assembly process not only improves gender equality in science and provides more collaborative opportunities for women, but also enhances teams' performance in terms of high-impact research production (53). With respect to patent-to-paper citations, for both types of teams, increasing team expertise diversity is associated with greater impact on patenting, especially when the team has four or more authors.…”
Section: Resultsmentioning
confidence: 99%
“…In their meta-analysis of 108 primary studies, Stahl, Maznevski, Voight and Jonsen (2010) concluded that the impact of cultural diversity on team performance is an indirect one that is mediated by ''creativity, cohesion, and conflict'' (process variables) and moderated by ''team tenure, complexity of the task' ' and ''co-located'' vis-a-vis ''geographically dispersed'' teams (contextual variables). A recent analysis of over 6.6 million papers published in the medical sciences since 2000 showed that despite the continued underrepresentation of gender-diverse research teams, while controlling for team size, the ''publications of mixed-gender teams are substantially more novel and impactful than the publications of same-gender teams of equivalent size'' (Yang, Tian, Woodruff, Jones & Uzzi, 2022). Novelty was gauged through an analysis of the paper's bibliographic references to suggest new knowledge combination relative to the existing literature, and impact was measured in terms of the ''top 5 percent of citations for papers published in a given year''.…”
Section: Research-paradigmatic and Cognitive Approachesmentioning
confidence: 99%